Current Limitation Method for V/f Control of Five-Phase Induction Machines. (31st January 2022) - Kyslan, Karol; Lacko, Milan; Ferková, Želmíra; Petro, Viktor; Padmanaban, Sanjeevikumar; Perduková, Daniela
Abstract : Five-phase induction machines (5pIMs) are a viable alternative for a wide range of industrial applications. The penetration of drives with 5pIM into industrial applications is slow because of the complexity of the proposed control algorithms. In standard V / f control of induction machines, the stator current is not controlled directly and options for current limitation are restricted. This paper hence addresses a novel current limitation technique for the V / f control algorithm of 5pIM. In addition, a simple speed sensorless control algorithm based on the slip compensation is introduced. A combination of both algorithms is suitable for low-cost medium-precision drive applications. Experimental results, realized on Texas Instruments F28335 DSP, illustrating the performance of novel current limitation technique and sensorless control, are included.